2015
DOI: 10.1515/reveh-2015-0001
|View full text |Cite
|
Sign up to set email alerts
|

Scientific evidence contradicts findings and assumptions of Canadian Safety Panel 6: microwaves act through voltage-gated calcium channel activation to induce biological impacts at non-thermal levels, supporting a paradigm shift for microwave/lower frequency electromagnetic field action

Abstract: AbstractThis review considers a paradigm shift on microwave electromagnetic field (EMF) action from only thermal effects to action via voltage-gated calcium channel (VGCC) activation. Microwave/lower frequency EMFs were shown in two dozen studies to act via VGCC activation because all effects studied were blocked by calcium channel blockers. This mode of action was further supported by hundreds of studies showing microwave changes in calcium fluxes and intracellular calcium [Ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
47
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(51 citation statements)
references
References 57 publications
(81 reference statements)
1
47
0
3
Order By: Relevance
“…Pulsed fields have often been found to be more biologically active than are non-pulsed fields in many different studies from many countries (Pall, 2015, Panagopoulos et al, 2013Belyaev, 2015) Nervous system regions impacted by non-thermal microwave and lower frequency fields include: cortex, diencephalon including the hypothalamus and thalamus, hippocampus, autonomic ganglia, sensory fibers, pituitary gland including neurohypophysis Neuroendocrine changes seem to undergo change over increased time of exposure. Neurosecretion in the hypothalamus and in the pituitary each go through a complex sequence over time, where EMF exposure initially produces increased hormone secretion but where over time, the neurosecretory cells become "exhausted", leading to lowered secretion and in some cases cell death (pp.77-96).…”
Section: Observations Including Page Numbersmentioning
confidence: 99%
See 2 more Smart Citations
“…Pulsed fields have often been found to be more biologically active than are non-pulsed fields in many different studies from many countries (Pall, 2015, Panagopoulos et al, 2013Belyaev, 2015) Nervous system regions impacted by non-thermal microwave and lower frequency fields include: cortex, diencephalon including the hypothalamus and thalamus, hippocampus, autonomic ganglia, sensory fibers, pituitary gland including neurohypophysis Neuroendocrine changes seem to undergo change over increased time of exposure. Neurosecretion in the hypothalamus and in the pituitary each go through a complex sequence over time, where EMF exposure initially produces increased hormone secretion but where over time, the neurosecretory cells become "exhausted", leading to lowered secretion and in some cases cell death (pp.77-96).…”
Section: Observations Including Page Numbersmentioning
confidence: 99%
“…Pilla (2012) showed that pulsed microwave field exposure, produced an almost instantaneous increase in calcium/calmodulindependent nitric oxide (NO) signaling, providing strong evidence that these fields can produce an almost instantaneous VGCC activation. It is likely, that these EMFs act directly on the voltage sensor of the VGCCs to produce VGCC activation (Pall, 2015) with the voltage sensor being exquisitely sensitive to these EMFs because of its physical properties and location in the plasma membrane.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…We will mainly focus on the eyes due to its sensitivity to electromagnetic fields [18][19][20][21][22]. This is because eyes are close to the antenna and directly exposed to the microwave without the protection of skin and fat.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, eyes have less blood flow which could not take the heat induced by microwave timely [20]. Thirdly, ocular tissues except the cornea do not have self-renewal ability, which could never grow back once hurt by the microwave [18,21,22]. A three-dimensional anatomicallybased human head CAD model and a pair of metallic frame glasses will be established based on the Finite Different Time Domain (FDTD) method.…”
Section: Introductionmentioning
confidence: 99%